Grain dust characterization and repeated handling in pilot-scale bucket elevator legs - Barretto, Roselle Paulasa (Kansas State University, 2021)
Moving and transferring grains in large quantities generate grain dust that poses both health and safety hazards. For the first study, two pilot-scale bucket elevator legs with front-feed and back-feed directions were used to examine the effect of repeated handling on soybean dust quantity, particle size, particle size distribution (PSD), and shape characteristics (high sensitivity (HS) circularity, aspect ratio (AR), and elongation). The effect of soybean grades [U.S. No. 1 and U.S. No. 3] and elevator types on various parameters was also studied. The dust samples were collected at different sampling points of the bucket elevator using glass fiber filters. Particle size and shape analysis were determined using the Malvern Morphologi G3 SE. Results showed significant differences (p<0.05) in the mass of dust collected (md) among soybean grades and elevator types in the first run. A general decreasing trend in md was observed for all elevator types and soybean grades with sampling points 1 and 2 having the highest md. The circle equivalent diameter of the dust particles ranged from 3.00 μm to 8.36 μm. Meanwhile, the overall PSD across grades, runs, and sampling points did not significantly vary (p>0.05). For the second study, dust samples from wheat, corn, soybean, rice, and milo were obtained and tested in five replicates for particle size, PSD, and shape characteristics (circularity, HS circularity, convexity, elongation, solidity, and AR) using Morphologi G3 SE. Flowability and floodability indices were determined using Carr indices chart based on aerated and packed bulk density (𝜌𝑝) measurements; angles of repose, spatula, fall, and difference; compressibility; cohesion; and dispersibility in the Hosokawa Powder Tester PT-R. Results showed significant differences in 𝜌𝑝, cohesion, elongation, and AR among the five grain dust types. Soybean dust exhibited the highest flowability (34.70) and floodability (64.25) indices while milo dust exhibited the lowest (flowability index, 11.60; floodability index, 9.70). Very strong positive correlation was observed for floodability index and dispersibility while very strong negative correlation was observed for cohesion and flowability index. Determining the flowability, floodability, and particle size and shape characteristics of various grain dust types is critical in the design of bulk handling equipment that may reduce the hazard associated with explosion and unexpected spills. Quantitative values of dust properties are also important as these provide the necessary data to construct modeling and simulation experiments of dust handling, emission, and explosion.
Keywords: Soybean dust characterization; Repeated elevator handling; Grain dust; Flowability and floodability; Particle size analysis; Bucket elevator